Efficient removal of anionic, cationic textile dyes and salt mixture using a novel CS/MIL-100 (Fe) based nanofiltration membrane. (December 2021) - Gnanasekaran, Gnanaselvan; Sudhakaran, M.S.P.; Kulmatova, Dilafruz; Han, Jeongho; Arthanareeswaran, G.; Jwa, Eunjin; Mok, Young Sun
Abstract: The purification of hazardous textile dyeing wastewater has exhibited many challenges because it consists of a complex mixture, including dyestuff, additives, and salts. It is necessary to fabricate membranes with enhanced permeability, fouling resistance, stability, and superior dyes and salts removal from wastewater. Incorporating a highly water stable metal-organic framework (MOFs) into membranes would meet the requirements for the efficient purification of textile wastewater. In this study, nanofiltration (NF) membranes are fabricated by incorporating MIL-100 (Fe) into the chitosan (CS) through film casting technique. The effect of MIL-100 (Fe) loadings on chitosan characterized by FT-IR, XRD, contact angle measurement, FESEM-EDS, XPS, zeta potential, and surface roughness analysis. The membrane characterization confirmed the enhanced surface roughness, pore size, surface charge, and hydrophilicity. The CS/MIL-100 (Fe) membrane exhibited an improved pure water flux from 5 to 52 L/m 2 h as well as 99% rejection efficiency for cationic methylene blue (MB) and anionic methyl orange (MO). We obtained the rejection efficiency trend for the MB mixed salts in the order of MgSO4 (Mg 2+ - 51.6%, SO4 2− - 52.5%) > Na2 SO4 (Na + - 26.3%, SO4 2− - 29.3%) > CaCl2 (Ca 2+ - 21.4%, Cl − - 23.8%) > NaCl (Na + - 16.8%, Cl − - 19.2%). In addition, the CS/MIL-100 (Fe) composite membrane showed excellent rejection efficiency and antifouling performances with high recycling stability. These stunning results evidenced that the CS/MIL-100 (Fe) nanofiltration membrane is a promising candidate for removing toxic pollutants in the textile dyeing wastewater. Graphical abstract: Graphical abstract of dye and salt removal by CS/MIL-100 (Fe) membrane. Image 1 Highlights: Hydrophilic MIL-100 (Fe) used as nanofillers for a novel composite membrane. CS/MIL-100 (Fe) composite enhanced the membrane permeability and rejection ability. CS/MIL-100 (Fe) membranes exhibited effective rejection of ions and dyes. CS/MIL-100 (Fe) membranes had good stability during the long-term test.